DEVELOPING PRAGMATIC COMPETENCE IN EFL LEARNERS THROUGH TASK-BASED LANGUAGE TEACHING (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Pragmatic competence constitutes a core dimension of communicative proficiency and remains an essential objective in EFL pedagogy. However, learners in foreign language contexts frequently exhibit deficiencies in their ability to perform speech acts appropriately due to limited exposure to naturalistic communication. This article investigates the potential of Task-Based Language Teaching (TBLT) as an effective methodological framework for enhancing pragmatic competence among EFL learners. Drawing on a qualitative action-research design with B2-level university students, the study demonstrates that task-based instruction fosters substantial gains in pragmalinguistic accuracy, sociopragmatic judgment, interactional fluency, and metapragmatic awareness. The findings highlight the pedagogical value of TBLT as a comprehensive approach to pragmatic instruction and underscore its relevance for contemporary EFL curricula.